2003
DOI: 10.1007/s00134-003-1800-5
|View full text |Cite
|
Sign up to set email alerts
|

Serum creatine kinase as predictor of clinical course in rhabdomyolysis: a 5-year intensive care survey

Abstract: In our cohort of patients with severe rhabdomyolysis the level of serum CK predicted the development of ARF. Although our results suggest that series of CK determination might be beneficial for the evaluation of the effect of therapy, the value of CK determination as a prognostic tool is limited, given the wide range of CK levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
125
1
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(146 citation statements)
references
References 21 publications
5
125
1
6
Order By: Relevance
“…Serum CK levels correlated with the onset of ARF, as these patients had significantly higher admission and peak CK concentrations. The conclusion of the study was that level of CK predicted the development of ARF in patients with severe rhabdomyolysis [10]. The finding was similar to our study, which showed that the initial value of CK predicted the development of ARF in patients with rhabdomyolysis.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Serum CK levels correlated with the onset of ARF, as these patients had significantly higher admission and peak CK concentrations. The conclusion of the study was that level of CK predicted the development of ARF in patients with severe rhabdomyolysis [10]. The finding was similar to our study, which showed that the initial value of CK predicted the development of ARF in patients with rhabdomyolysis.…”
Section: Discussionsupporting
confidence: 87%
“…In a study done by de Meijer et al [10], 26 patients with severe rhabdomyolysis were taken into the study and their clinical and laboratory data were reviewed. It was found that mean CK level was 38,351±34,354 U/L on admission and rose further in all patients (mean 59,147±67,514 U/L).…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have reported similar findings. [7][8][9] Serum CK may be useful for the diagnosis of crush injury, rather than for risk stratification.…”
Section: Discussionmentioning
confidence: 99%
“…Reported use of blood enzyme markers is common throughout the surgical literature [9,12,[16][17][18][20][21][22][23][24]. Rhabdomyolysis has numerous etiologies and includes local crush injury, vascular compromise, soft tissue infections, electrical injuries, excessive steroid use, seizures, surgery, and heat stroke [1,19,22].…”
Section: Discussionmentioning
confidence: 99%
“…Creatine kinase is a naturally occurring enzyme with the greatest concentrations found in skeletal muscle, cardiac muscle, and the brain [9,19]. Myoglobin also is found in cardiac and skeletal muscle and is released into the circulation when muscle is damaged through disease, exertion, or trauma and is excreted in the urine [9,16,19,20,22]. The use of serum markers, including CK, CPK, and serum myoglobin, may allow for an objective evaluation of the potential advantages among various MIS techniques.…”
Section: Discussionmentioning
confidence: 99%